Glucagon-Like Peptide-1 Receptor Agonist Use and Risks of Hospitalization and Mortality in Patients with End-Stage Kidney Disease - Steph Karpinski; Rizwan Qazi; Terrence Bjordahl; Scott Sibbel; Eric Weinhandl; Francesca Tentori; Steven M. Brunelli (Clinical Journal of the American Society of Nephrology, 2026)
Background: The recent clinical trial FLOW showed that semaglutide, a Glucagon-Like Peptide-1 Receptor Agonist (GLP1-RA), reduced the risk of clinical outcomes and death from cardiovascular causes in patients with chronic kidney disease (CKD) and type 2 diabetes. Given the substantial benefit to patients with CKD, the question remains whether these drugs benefit patients with end-stage kidney disease (ESKD). We sought to evaluate the impact of GLP-1RA use in incident ESKD patients on clinical outcomes. Methods: Patients included in this matched retrospective cohort study were adult ESKD patients who initiated thrice-weekly in-center hemodialysis (ICHD) at a kidney care organization between January 2018 and April 2024. Using internal electronic health record (EHR) data, eligible patients who initiated dialysis on a GLP-1RA (with evidence of a GLP-1RA prescription in the first 30 days after dialysis initiation; n=2,492) were matched 1:1 to those not on a prescription. Patients were followed from index date until death or the end of the study (July 31, 2024). Incident rate ratios were estimated using a negative binomial distribution with a random intercept to account for the matched nature of the data. Results: Patients with a GLP-1RA prescription in the first month of dialysis had a mean±SD age of 63±12 years old and were predominately male (59%). Compared to other eligible dialysis patients, nearly all patients on a GLP-1RA had a known diagnosis of diabetes (98% vs. 73%), a majority had evidence of predialysis nephrology care (76% vs. 67%), were of White race (46% vs. 39%), and had a mean±SD BMI of 33±8 kg/m 2 (vs. 30±8). After matching and adjustment, GLP-1RA’s were independently associated with lower hospitalization [IRR: 0.91 (0.87, 0.96)] and mortality [IRR: 0.83 (0.73, 0.95)] rates. Conclusions: Among incident ICHD patients, GLP-1RA use was independently associated with a 9% lower hospitalization rate and a 17% lower mortality rate.